Successful Treatment of Rare Cause of Mastitis (Pseudomonas Sp.) in a Transition Cow - M.Venkatesan; K. Jayalakshmi; A.Ramya; R.Ravi; D. Sumathi; K.K. Ponnu Swamy (The Indian Veterinary Journal, 2024)
A Holstein Friesian cross-bred cow with two calving presented to a large animal medical outpatient unit in the Veterinary Clinical Complex, Veterinary College and Research Institute, Namakkal with a history of loss of appetite, swelling of right fore and hind quarter and with orange-colored flakes in the milk. Physical examination revealed no systemic abnormality. Affected quarter milk was collected for culture and revealed pseudomonas infection. The animal was continuously treated with Gentamicin and Enrofloxacin based on ABST for a week and uneventfully recovered after ten days.